Description of two new pseudocerotids (Rahabditophora: Rhabditophora; Polycladida) from Andaman & Nicobar Islands, India - Dixit, Sudhanshu; Sivaperuman, C.; Raghunathan, C. (Zootaxa, 2018)
The genus Pseudoceros is one of the flashiest among polyclads and is represented by 93 species worldwide while the genus Acanthozoon consists of polyclads with papillae and 14 valid species distributed around the world. Pseudoceros meenae sp. nov. and Acanthozoon fuscobulbosum sp. nov., based on morphological and histological characters have been described in the present paper. Pseudoceros meenae sp. nov. is characterised by white to cream body with three marginal bands; inner black, middle orange and a white rim while and Acanthozoon fuscobulbosum, sp. nov. is characterised by numerous brown and bulbous papillae of variable sizes on dorsum.